Co-operation, trust and Triple Helixes in a Northern dimension - Ylinenpää, Håkan (Luleå tekniska universitet, Innovation och Design, 2001)
Regional development in a knowledge-based economy to a higher degree than in a traditional industrial society requires co-operation between (i) industry and trade, (ii) knowledge centres such as universities, and (iii) government bodies on different levels. A knowledge-based economy thus involves new challenges for regional development. For peripheral regions at the outskirts of an integrated European economy, overcoming spatial disadvantages adds to the list of challenges for actors involved in regional development. Established theoretical wisdom, however, seem to have difficulties in providing guidance and advice how to achieve favourable conditions for a dynamic development of such regions. This has fostered an interest in ‘bench-learning', i.e. learning from regions that seem to ‘have made it' regardless of geographical disabilities. This article applies a Triple Helix perspective on the development of two Nordic regions: the Luleå region in Sweden and the Oulu region in Finland. The article discusses how the development in these two regions may be understood from a Triple Helix perspective. The article concludes with a discussion on the prospects to develop Triple Helix co-operation in Northwest Russia, specifically pinpointing the need to build trust among key actors in the economy. Godkänd; 2001; Bibliografisk uppgift: Paper presented at the ‘Think-tank seminar on the Northern Dimension and the Future of the Barents Euro-Arctic Co-operation” in Björkliden Mountain Centre, Swedish Lapland, June 14–17, 2001. Även publicerad i "International perspectives on the future of the barents euro-arctic region and the northern dimension", Länsstyrelsen i Norrbottens län 2001; 20070701 (ysko)